FLOW UNIT IDENTIFICATION OF ZELDA MEMBER SANDSTONE RESERVOIR, TALANGAKAR FORMATION, CINTA FIELD, SUNDA BASIN - YOGAPURANA, ERIK
Cinta Field is a mature oil field that has been operated since 1970. Located in the southern part of Sunda Basin, this field already produces cummulative oil 258 MMBO from clastic reservoir of Zelda Member. Future water injection and redevelopment plans of this field as the consequence, require detail analysis through static and dynamic approaches. This thesis focuses on the flow unit identification through petrophysical rock typeÃ‚Â–based static reservoir characterization. Hence by identification of rock type, its composition and distribution, a comprehensive understanding of the petrophysical properties of the reservoir and its influence to reservoir flow capacity can be achieved. Core data with a total length of 494 ft from seven wells, 932 core plugs which each of them was measured for its porosity and permeability, combined with 115 wells data were used in this study. Facies, facies association and diagenetic analyses are performed to understand the influence of facies, depositional environments and diagenesis to the development of petrophysical rock types (PRT). Petrophysical analysis plays most important role in the identification of flow unit by defining the rock types through RQI/FZI approaches, where each rock types are represented by a unique porosity and permeability relationship with high correlation coefficient. Five rock types are identified within Zelda Member reservoir: PRT 1 which is representation of non-reservoir litofacies such as shale, PRT 2 which representation of siltstone litofacies, PRT 3 as a representation of fine grained sandstone and laminated sandstone litofacies with good cementation, PRT 4 as a representation of poorly sorted sandstone litofacies characterized by medium level of cementation, and the last is PRT 5 which is representation of poorly cemented of conglomeratic sandstone and poorly sorted sandstone litofacies characterized by its loose fragment of sand grain. Three-dimensional reservoir characterization through 3-D reservoir modeling was performed for facies, PRT and PRT-constrained porosity and permeability models. The modeling results show strong consistency between petrophysical properties and the underlying rock type models. High porosity and permeability values are mostly in association with good reservoir quality rock types, those are PRT 4 and PRT 5. Validation of permability model shows similar trend with permeability value from core data, and the most is the permeability model results match with the permeability derives from production test of two DST wells.